Transcatheter Closure of Perimembranous Ventricular Septal Defect with Aneurysm: Radiologic Characteristic and Interventional Strategy - Weibing Guo; Yifan Li; Jinjin Yu; Junjie Li; Ling Sun; Jijun Shi; Shushui Wang; Hong Chen; Zhiwei Zhang (Journal of Interventional Cardiology)
Objectives. We aimed to explore the radiologic characteristics and interventional strategies for perimembranous ventricular septal defect (pmVSD) with aneurysm. Methods. 257 patients who underwent transcatheter closure of pmVSD with aneurysm were included in our study. We retrospectively reviewed the left ventricular opening of the aneurysm (a), diameter of the midsegment of the aneurysm (b), and diameter of the right ventricular opening of the aneurysm (c). If there were multiple defects within the aneurysm, the largest defect was denoted as c1 and so forth. We developed a novel VSD classification method in which pmVSD with aneurysm was classified into three types (A, B, and C). When a >b ≥ c, it was classified as type A, when b > a ≥ c, it was type B, and when c > a ≥ b, it was type C; c/c1 described the relationship among defects. Results. All of the 257 cases of pmVSD with aneurysm were defined using left ventriculography: type A, 60, type B, 58, and type C, 139. Transcatheter closure was attempted in 244 patients and succeeded in 227 cases (success rate was 93.0%; 227/244). Forty symmetric VSD occluders and 13 asymmetric VSD occluders were used for type A aneurysm occlusion; 31 symmetric VSD occluders, 19 asymmetric VSD occluders, and one Amplatzer duct occluder II (ADOII) were used for type B; 59 VSD symmetric occluders, 59 asymmetric VSD occluders, three eccentric VSD occluders, and two ADOII were used for type C. Within 24 hours after procedure, 2.2% patients had postprocedural residual shunt, and 2.2% experienced malignant arrhythmia (including type II second-degree AVB, cAVB, and CLBBB). Two hundred and twelve patients completed follow-up (93%, 212/227). No new severe complications were reported during follow-up, except in one patient who underwent surgery (removal of the device, VSD repair, and tricuspid valvuloplasty) due to severe postprocedural tricuspid regurgitation. Conclusions. It is safe and effective to apply this method for the classification of pmVSD with aneurysm and its interventional strategy.